Anaerobic Digestion untuk Pengolahan Sampah Organik: Analisis Multikriteria Menggunakan Metode Analytic Network Process - Mochammad Chaerul; Yahdini Qornin Mardiyah (Jurnal Serambi Engineering, 2019)
Organic waste can be treated through anaerobic digestion in a bioplant facility. Different management  attern of bioplant has different consequences to each criterion affecting the sustainability of the bioplant. The study aims to apply multicriteria analysis using Analytic Network Process (ANP) method to alternatives of the bioplant management available in Bandung City as a case study. Multicriteria developed in the study, namely Technical, Environment, Social, and Economic, have their respective subcriterions to be analyzed further through interview to related stakeholders. The result revealed that the following subcriterions had the highest driving power and dependency: construction and operational, pretreatment, and availability of infrastructure  (Technical criterion), amount of labor required, readiness of community for waste segregation (Social), and  investment and operational costs (Economic). All subcriterions in criterion of Environment were deemed not so important. The best alternative choosen was a bioplant with waste segregation by generator at source and supported with waste bank